Host bacterial community of MGEs determines the risk of horizontal gene transfer during composting of different animal manures. (July 2019) - Zhu, Longji; Zhao, Yue; Yang, Kangjie; Chen, Jian; Zhou, Haixuan; Chen, Xiaomeng; Liu, Qi; Wei, Zimin
Abstract: Mobile genetic elements (MGEs) play critical roles in transferring antibiotic resistance genes (ARGs) among different microorganisms in the environment. This study aimed to explore the fate of MGEs during chicken manure (CM) and bovine manure (BM) composting to assess horizontal transfer risks of ARGs. The results showed that the removal efficiency of MGEs during CM composting was significantly higher than that during BM composting, because the potential host bacteria of MGEs were eliminated largely during CM composting. Meanwhile, these potential host bacterial communities are significantly influenced by pH, NH4 +, NO3 − and total N, which can be used to regulate host bacterial communities to remove MGEs during composting. Projection pursuit regression further confirmed that composting can effectively reduce the horizontal transfer risk of ARGs, especially for CM composting. These results identified the critical roles of host bacterial communities in MGEs removal during composting of different animal manures. Graphical abstract: Image 1 Highlights: The removal rate of MGEs was higher in CM composting than that in BM composting. The potential host bacteria of MGEs were almost eliminated during CM composting. The pH, NH4 +, NO3 − and total N can regulate MGEs removal during composting. Fresh CM was confirmed to have greater risk for HGT in comparison with BM. Abstract : Host bacterial community of MGEs determines the risk of horizontal gene transfer during composting of different animal manures.